Identification of Soil Transmitted Helminths Eggs on Flies in KM 5 Market, Palembang City - Husna Syafira Muthmainnah; Gita Dwi Prasasty; Dalilah Dalilah; Dwi Handayani; Susilawati Susilawati (Sriwijaya Journal of Medicine, 2021)
The prevalence of Soil Transmitted Helminths (STH) infection in the world is still high, especially in areas with poor sanitation. This condition is often found in markets which becomes a favorite place for flies. Flies are insects that have the ability to fly far and habits of life that move around so they can become human health problems as mechanical vectors of STH infection. Therefore, this study aimed to find out the type and number of flies, and the contamination of STH eggs in flies in Pasar KM 5 Palembang City. This research was an observational descriptive study with a cross sectional design. The samples of this study were caught with accidental sampling using insect nets and fly traps. The samples processing and observation were made at the Biooptic and Chemistry Medic Laboratory, Faculty of Medicine Sriwijaya University. The number of flies obtained 419 flies and consisted of 136 Musca domestica (32.4%), 183 Chrysomya megacephala (43.7%), and 100 Lucilia sp. (23,9%). From 42 total samples studied, 14 samples positively contaminated with STH eggs (33.4%), that consisting of 3 samples of Musca domestica (7.2%), 6 samples of Chrysomya Megacephala (14.3%), and 5 samples of Lucilia sp. (11,9%). The number of STH eggs obtained 17 eggs, consisted of 16 eggs of Ascaris lumbricoides (94.1%) that was 3 eggs in Musca domestica (17.7%), 7 eggs in Chrysomya megacephala (41.1%), and 6 eggs in Lucilia sp. (35.3%), and 1 egg of Trichuris trichiura in Chrysomya megacephala (5.9%). The conclusion was that there was contamination of STH eggs on flies in KM 5 Market Palembang City.